2018
DOI: 10.5546/aap.2018.eng.e54
|View full text |Cite
|
Sign up to set email alerts
|

Brain death and organ donation in Argentine pediatric intensive care units. A multicenter study

Abstract: Brain death (BD) is a condition determined by the complete and irreversible absence of brain functions. Maintenance of vital functions creates an opportunity for organ donation. A retrospective study was carried out in 7 pediatric intensive care units of Argentina (from 1/1/2013 to 9/30/2016) to determine the incidence of clinical and certified BD, and the proportion of effective transplantations. Among deceased patients, 19.14% (147/768) met the clinical requirements for BD, and the main cause of BD was multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The recipient-to-donor ratio (solid organs) in their study was close to 4. 14 This ratio was 2 : 5 in Brierly’s study. 28 In our study, the recipient-to-donor ratio was found to be 2 : 6 (13 solid organs per 5 donors), which is comparable to the existing literature.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…The recipient-to-donor ratio (solid organs) in their study was close to 4. 14 This ratio was 2 : 5 in Brierly’s study. 28 In our study, the recipient-to-donor ratio was found to be 2 : 6 (13 solid organs per 5 donors), which is comparable to the existing literature.…”
Section: Discussionmentioning
confidence: 75%
“…They also revealed that the combination of EEG and AT was the most used ancillary method, in about 65% of their study cohort, like the observation in our study. 14 Aslan et al 18 from Turkey reported similarly high rates of ancillary tests in their study group, including 20 pediatric BD cases. In their report, they showed that they routinely use EEG and AT in 19 out of 20 patients, whereas CTA/MRA was applied to 8 patients (40%).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Organ procurement is the process of collecting organs and tissues for transplantation to meet the needs of patients on transplant waiting lists. ( 1 ) A great number of health care professionals (HCPs) take part in this process, both at the in-hospital and out-of-hospital levels. The high demand for transplant organs does not match the number of actual organ donors, and this shortage of organs is the leading cause of death among patients on transplant waiting lists.…”
Section: Introductionmentioning
confidence: 99%